Locals’ Participtaion In The Development Of The Holistic Integrative Early Childhood Education (Ecd) Service At Paud Pelangi Post, Pedalangan, Banyumanik Semarang Regency - Alfiana, Riza; Latiana, Lita (BELIA: Early Childhood Education Papers, 2016)
The background of the research is based on many cases of the Early Childhood Education (ECD) institutions which provide its service to early childhood students within limited time range only. This resulted the government to act by the release of ECD development policy through holistic integrative approach that includes health, nutrient, nurture, care, and protection in 2003. To support the enhancement of the access and quality of the Holistic Integrative ECD service, locals have a very vital role. This research employs qualitative descriptive method. The research subject of the research is locals, teachers, and principal. The data collection employs observation and interview. The data analysis uses data reduction, data presentation, and conclusion deduction and verification. The result of the results shows that (1) Holistic Integrative ECD service at PAUD Pelangi Post, Pedalangan specifically in giving service to their students to ensure the essential needs of the students is fulfilled, in the practice of the Holistic Integrative ECD program has been done well and successfully. PAUD Pelangi Post has given and prepared what are needed by students through integrative holistic service, both in giving facilities and infrastructure. (2) Locals’ participation in the development of Integrative Holistic ECD service at PAUD Pelangi Post is in the level of planning in balancing the ideas in the form of Posyandu and PMT reinforcement; implementing through sending their children to school from early childhood, following Bina Keluarga Balita (BKB), parenting, participating in Posyandu, and donating voluntarily; and supervising by reporting problems of children’s development to the principal and school through Puskesmas (Health institution) to find the best solution, hence children could get the best care from the best party. Locals’ participation arises due to self-awareness, outside reinforcement, and out of habit. The recommendations of the research are as follow: (1) the local to actively contribute and participate in the effort to equip the ECD institution with facilities and infrastructure to maximize service, (2) the school to develop their Holistic Integrative ECD service that is integrated with Posyandu and Bina Keluarga Balita (BKB), but also actively participate in activities within the area.